Effect of Quality Improvement Approaches on Prevention of Mother to Child Transmission Services Coverage in Nairobi County - Malava, Duece N.; Muriithi, Peterson; Barasa, Chrisostim (International Journal of Innovative Research in Medical Science, 2021)
Background: Improving the quality of healthcare is a growing international concern as it ensures that the healthcare system functions efficiently. Quality improvement in the HIV field focuses on achieving essential health outcomes, including patient retention, increasing viral load suppression, and improving overall health outcomes of people living with HIV. Quality Improvement (QI) approaches form part of the global strategies recommended by WHO to improve prevention of mother to child transmission (PMTCT) coverage and to achieve virtual elimination of mother to child transmission (MTCT). Nairobi County is implementing QI approaches using the Kenya Quality Model for Health (KQMH) framework. The implementation of QI began in January 2016, and since then, the facilities have formed work improvement teams (WITs) that work to improve the quality in the facilities. Study objective: This study sought to evaluate the effect of quality improvement approaches on PMTCT coverage in Nairobi County. Methodology: This quasi-experimental study applied a mixed-method research methodology. Purposive sampling determined the four study facilities. The participants were women attending the PMTCT clinic at the selected facilities, identified through a purposive sampling process. DHIS reports and facility registers provided the necessary quantitative data, while Focus Group Discussions (FGDs) and Key informant interviews (KIIs) provided qualitative data. Quantitative data showing service delivery uptake over time provided a trend on the performance of the key indicators under study. This data analysed using an interrupted time series approach as well as by using descriptive statistics showed trends over time. Qualitative data assessed clients’ experiences while accessing PMTCT services, providing key insights from the clients’ perspective. The researcher used content analysis to analyse this data. Results: The study found out that quality improvement is an integral part of PMTCT service delivery. Through the FGDs, the PMTCT services provided generally satisfy the clients’ needs, and that the clients have a significant role in quality improvement. The HCWs can implement QI approaches as long as they have the facility management's support and leadership. Conclusion: The study found out that quality improvement in PMTCT relies heavily on the systems being in place and on teamwork between the HCWs and clients as they access treatment services at the health facilities.